Volume 2: Combustion, Fuels and Emissions, Parts a and B 2010
DOI: 10.1115/gt2010-23689
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Combustion-Generated Particles at Tropospheric Conditions

Abstract: This paper describes particle evolution measurements taken in the Particulate Aerosol Laboratory (PAL). The PAL consists of a burner capable of burning jet fuel that exhausts into an altitude chamber that can simulate temperature and pressure conditions up to 13,700 m. After presenting results from initial temperature distributions inside the chamber, particle count data measured in the altitude chamber are shown. Initial particle count data show that the sampling system can have a significant effect on the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…In our model, a semi-empirical correlation describing the mixing of an axisymmetric jet in a co-flowing ambient fluid (Nickels and Perry, 1996) was used to evaluate the plume's centerline properties. The calculated exhaust plume's centerline temperature, velocity, and dilution ratio as a function of downstream distance were found to be consistent with experimental data collected in the chamber (Tacina and Heath, 2010). The contribution of microphysical processes is further divided into contributions of (1) homogeneous nucleation of new liquid particles, (2) coagulation between liquid particles, (3) activation of hydrophobic soot surfaces, (4) condensational growth of water vapor on soot particles, and (5) heterogeneous freezing of liquid coated soot particles: In our model, homogeneous nucleation of new liquid particles is described by the kinetic quasi-unary nucleation theory developed by Yu (2005Yu ( , 2006Yu ( , 2007.…”
Section: Modeling Methodologiessupporting
confidence: 62%
See 3 more Smart Citations
“…In our model, a semi-empirical correlation describing the mixing of an axisymmetric jet in a co-flowing ambient fluid (Nickels and Perry, 1996) was used to evaluate the plume's centerline properties. The calculated exhaust plume's centerline temperature, velocity, and dilution ratio as a function of downstream distance were found to be consistent with experimental data collected in the chamber (Tacina and Heath, 2010). The contribution of microphysical processes is further divided into contributions of (1) homogeneous nucleation of new liquid particles, (2) coagulation between liquid particles, (3) activation of hydrophobic soot surfaces, (4) condensational growth of water vapor on soot particles, and (5) heterogeneous freezing of liquid coated soot particles: In our model, homogeneous nucleation of new liquid particles is described by the kinetic quasi-unary nucleation theory developed by Yu (2005Yu ( , 2006Yu ( , 2007.…”
Section: Modeling Methodologiessupporting
confidence: 62%
“…The exhaust temperature at the nozzle tip (T ex ) was set at 350 K and the chamber background temperatures (T b ) were set to the values listed in Table 1. This scaling law was found to be robust in laboratory buoyant jets in coflowing fluids, and our previous experimental work showed that it is valid in the PAL chamber (Tacina and Heath, 2010). Following Eq.…”
Section: Ranges Of the Parameters Examinedmentioning
confidence: 99%
See 2 more Smart Citations
“…This paper discusses results from our coupled laboratory and modeling investigation of the effects of water and soot emissions and ambient conditions on the near-field formation of contrail ice particles. The Particle Aerosol Laboratory (PAL) at the NASA Glenn Research Center (Tacina and Heath, 2010) was employed to simulate a broad range of conditions that bracket those found in the exhaust from aircraft engines at cruise altitudes. The Aerodyne microphysical parcel model for contrail ice particle formation (Wong and Miake-Lye, 2010) was used to guide experimental de-sign and analyze experimental results.…”
mentioning
confidence: 99%